2017
DOI: 10.1021/acsami.7b04038
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Carbonic Anhydrase IX Targeting Ligand-Functionalized Porous Silicon Nanoplatform for Dual Hypoxia Cancer Therapy and Imaging

Abstract: Hypoxia occurs in most solid tumors, and it has been shown to be an independent prognostic indicator of a poor clinical outcome for patients with various cancers. Therefore, constructing a nanosystem specifically targeting cancer cells under hypoxia conditions is a promising approach for cancer therapy. Herein, we develop a porous silicon (PSi)-based nanosystem for targeted cancer therapy. VD11-4-2, a novel inhibitor for carbonic anhydrase IX (CA IX), is anchored on PSi particles (VD-PSi). As CA IX is mainly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 69 publications
3
27
0
Order By: Relevance
“…Rabies virus glycoprotein (RVG) conjugation of PSi loaded with siRNA was investigated as potent brain targeting drug carrier, and the monitor of the emission from a Dy677 tag attached to the siRNA payload showed that the RVG–PSi construct delivered a substantial quantity of siRNA to the injured site and can reach up to threefold more accumulation in damaged brain tissue comparing to healthy brain (Figure b) . A carbonic anhydrase IX (CA IX, 3‐(cyclooctylamino)‐2,5,6‐trifluoro‐4‐((2‐hydroxyethyl)sulfonyl)benzenesulfonamide) targeting ligand‐functionalized PSi showed high affinity toward cancer cells under hypoxia condition, which presented potent application into cancer targeting . PSi surface biofunctionalization was developed for tumor associated endothelial cells and in macrophages targeting.…”
Section: Surface Chemistry and Modification Of Psimentioning
confidence: 99%
See 1 more Smart Citation
“…Rabies virus glycoprotein (RVG) conjugation of PSi loaded with siRNA was investigated as potent brain targeting drug carrier, and the monitor of the emission from a Dy677 tag attached to the siRNA payload showed that the RVG–PSi construct delivered a substantial quantity of siRNA to the injured site and can reach up to threefold more accumulation in damaged brain tissue comparing to healthy brain (Figure b) . A carbonic anhydrase IX (CA IX, 3‐(cyclooctylamino)‐2,5,6‐trifluoro‐4‐((2‐hydroxyethyl)sulfonyl)benzenesulfonamide) targeting ligand‐functionalized PSi showed high affinity toward cancer cells under hypoxia condition, which presented potent application into cancer targeting . PSi surface biofunctionalization was developed for tumor associated endothelial cells and in macrophages targeting.…”
Section: Surface Chemistry and Modification Of Psimentioning
confidence: 99%
“…One common method is by conjugating fluorescence dye on the surface. Janoniene et al applied one fluorescence ligand, 3‐(cyclooctylamino)‐2,5,6‐trifluoro‐4‐((2‐hydroxyethyl)sulfonyl)benzenesulfonamide (VD11‐4‐2), into the surface modification of PSi. This is a fluorescence compound with maximum emission wavelength at 500 nm while the λ ex of DOX is 490 nm.…”
Section: Surface Chemistry and Modification Of Psimentioning
confidence: 99%
“…pSi is an attractive material for the delivery of cytotoxic chemotherapeutics. There have been numerous reports on the delivery of chemotherapy drugs using pSiNPs with great efficacy . Recently, Santos has given an overview of chemotherapy using pSi; therefore, this review will focus on tackling anticancer drug resistance by means of combination therapy…”
Section: Psi For Drug Deliverymentioning
confidence: 99%
“…24 Interestingly, different molecules have been developed to visualize hypoxic areas by the use of in-vivo imaging of CA9. [25][26][27][28] Here, we have demonstrated that CA9 is normally expressed at high and even levels in normal gallbladder epithelium, and was conserved at high levels in half of the GBC cases. Therefore, CA9 represents a promising candidate for theranostic strategies in GBC.…”
Section: Discussionmentioning
confidence: 61%
“…CA9 catalyses the reversible hydration of carbon dioxide; therefore, it has been studied as a potential target for cancer, as it is enriched in hypoxic niches of neoplastic tissues . Interestingly, different molecules have been developed to visualize hypoxic areas by the use of in‐vivo imaging of CA9 . Here, we have demonstrated that CA9 is normally expressed at high and even levels in normal gallbladder epithelium, and was conserved at high levels in half of the GBC cases.…”
Section: Discussionmentioning
confidence: 82%